An Image-Based Gradation Calculation Method considering Crushed Stone Morphology. (20th July 2022) - Jiang, Chong; Ding, Xin; Pang, Li; Deng, Liang; Shi, Zexiong
Abstract : An image-based gradation calculation method considering crushed stone morphology is proposed in this paper. Eight kinds of crushed stones are prepared to figure out the effect of the particle shape on the gradation. All particles are pictured, and the photos are processed to obtain particle shape indices by using the image-based method. A minimum Feret diameter analysis method is used, which can reflect the influence of the particle shape. Then, the paper proposes a developed overall regularity to describe the morphology of particles, which is calculated by the weight of three shape indices: aspect ratio, convexity, and sphericity. The developed overall regularity is applied on gradation curve equations to provide an image-based gradation calculation method. And the provided method is validated to well fit the actual case. Furthermore, the method is also applied on two examples of gradation designation and the result proves to be feasible and practicable.